Impact of Spasticity on Balance Control during Quiet Standing in Persons after Stroke. (14th September 2017) - Rahimzadeh Khiabani, Reza; Mochizuki, George; Ismail, Farooq; Boulias, Chris; Phadke, Chetan P.; Gage, William H.
Abstract : Background . Balance impairments, falls, and spasticity are common after stroke, but the effect of spasticity on balance control after stroke is not well understood. Methods . In this cross-sectional study, twenty-seven participants with stroke were divided into two groups, based on ankle plantar flexor spasticity level. Fifteen individuals with high spasticity (Modified Ashworth Scale (MAS) score of ≥2) and 12 individuals with low spasticity (MAS score <2) completed quiet standing trials with eyes open and closed conditions. Balance control measures included centre of pressure (COP) root mean square (RMS), COP velocity, and COP mean power frequency (MPF) in anterior-posterior and mediolateral (ML) directions. Trunk sway was estimated using a wearable inertial measurement unit to measure trunk angle, trunk velocity, and trunk velocity frequency amplitude in pitch and roll directions. Results . The high spasticity group demonstrated greater ML COP velocity, trunk roll velocity, trunk roll velocity frequency amplitude at 3.7 Hz, and trunk roll velocity frequency amplitude at 4.9 Hz, particularly in the eyes closed condition ( spasticity by vision interaction). ML COP MPF was greater in the high spasticity group. Conclusion . Individuals with high spasticity after stroke demonstrated greater impairment of balance control in the frontal plane, which was exacerbated when vision was removed.